Impact of tourism activities on the distribution and pollution of soil heavy metals in natural scenic spots on the northern slope of Tianshan Mountain - Jianjun Yang; Huan Xu; Xinjun Wang (PLoS ONE, 2022)
Human activities can significantly impact the natural ecosystem. As an important part of terrestrial ecosystems, soil participates in energy and material cycle. With the continuous intensification of human activities, soil undergoes increasingly serious disturbance. Under the influence of global change and human activities, the variability of heavy metals in soil is worthy of further discussion. Taking Lujiaowan and Juhuatai Scenic Spot on the northern slope of Tianshan Mountain as the research area, this study investigated the concentrations of Pb, As, Zn, Cu and Mn in the soil and analyzed their distribution and pollution levels. Meanwhile, the main sources of soil heavy metals were explored using autocorrelation analysis and principal component analysis. Results showed that the order of the average concentration of heavy metals in the study area was as follows: Mn> Zn> Cu> Pb> As. None of them exceeded the national soil environmental quality level II standard, and the average concentrations of Zn, Cu, and As exceeded the background value of Xinjiang soil, reaching a light pollution level. In addition, the distribution of heavy metals in soil displayed a regular trend, and a positive correlation was found between disturbance intensity and heavy metal concentration. The geoaccumulation index also showed that the five heavy metals in the study area had lower pollution degree compared with the background value in Xinjiang. The order of potential ecological risk was As > Cu > Pb > Zn > Mn.